A Beginner’s Guide to Water Management — Color - Florida LAKEWATCH (EDIS)
Aside from water clarity, the color of water in a lake is one of the main attributes that captures people's attention—particularly if the color begins to change. As this circular explains, changes in color can affect the biological productivity of a waterbody including the abundance of aquatic plants and/or algae. However, readers will also learn that most of these changes are the result of natural processes that occur within the watershed. Related topics of discussion include apparent color, true color, suspended and dissolved substances, along with the dynamics of light refraction. The last section provides two empirical models (equations) that can be used to determine if color in a waterbody is the result of algae or suspended solids.  This document, CIR108, is the eighth of a series of information circulars dedicated to familiarizing citizens with the language and techniques used by those involved in water management. © January 2004, 1st Edition.